Can BRICS De-dollarize the Global Financial System? - Zoe Liu, Zongyuan (Social Sciences, 2022)
This study develops a 'Pathways to De-dollarization' framework and applies it to analyze the institutional and market mechanisms that BRICS (Brazil-Russia-India-China-South Africa) countries have created at the BRICS, sub-BRICS, and BRICS Plus levels. This title is also available as Open Access on Cambridge Core.